Exploring the Correlation between Testosterone Levels and ICSI Fertilization and Embryo Development Success in Women - Ismael, Ismael; Ibrahim, Khaleel; Ban Thabit, Al-Ani,; Jassim, Wasan Hamad; Rana R, Al-Saadi, (Journal of Neonatal Surgery, 2025)
This work aims to establish the correlation between the described hormone—testosterone—and the effectiveness of ICSI fertilization and embryonal formation in females. It has been established that testosterone is a male androgenic hormone, but this hormone is also important to the female reproductive system. It plays a part in the process of follicular growth in the ovaries, oocyte completion of meiosis, and also in the quality of the oocytes collected for ART. Abnormal concentrations of testosterone appear to interfere with folliculogenesis, decrease the likelihood of fertilization, as well as compromise the development of the embryo. This study aims to present a causal relationship between testosterone and ICSI result parameters, such as fertilization rate, quality of embryos, and implantation competence. Clinical and laboratory data were descriptive and comparative to check the existence of statistically significant patterns or relationships utilizing regression analysis. The results showed that a moderate T level is good for the QOL and the viability of the embryos, but both high and low levels have impacts on the success rates. These insights argue for hormonal profiling prior to the onset of ICSI cycles. They may have a significant impact on increasing ART success rates and decreasing the stress and expense of infertility treatments if conducted specifically according to testosterone levels. Thus, the findings of this dissertation serve a significant purpose of enriching the literature on the need to adopt individualized hormonal strategies in ART treatment plans to enhance results (Alshehre et al., 2020).